Pengaruh Pijat Bayi Terhadap Kenaikan Berat Badan Pada Bayi Usia Kurang Dari 6 Bulan Tahun 2022 - Wahyuni, Dwi Reza; Khoiriah, Restu (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Infant massage is a direct contact touch therapy with the body that can provide a sense of security and comfort for babies. The purpose of the study to determine the effect of infant massage on weight gain in infants less than 6 months in PMB E. This study uses a quasi-experimental approach with a pre-post-test design approach. To see the effect before and after the intervention given by the researcher. Based on the results of the study, it showed that there was an effect between giving baby massage before and after the baby's weight less than 6 months in PMB E. This is evidenced from the results of the analysis which shows that the p-value less than 0.005. there is an effect of infant massage on the weight gain of infants less than 6 months in